Analyze the Role of Job Satisfaction and Motivation in Shaping Driver Performance at PT. ASA - Bintang Narpati (Universitas Trisakti, 2024)
This study analyzes the role of job satisfaction and motivation in shaping employee performance, focusing on drivers at a logistics transportation company in Bekasi Regency. Driver performance is a crucial factor for the company's success because it affects customer satisfaction and operational effectiveness. Problems that often arise include absenteeism, delay, and inaccuracy in the delivery of goods. This study uses a quantitative method with multiple linear regression analysis techniques to test the relationship between job satisfaction and motivation to performance. The results of the validity and reliability test showed that the two independent variables had a significant influence on the bound variables. The partial test (t-test) revealed that job satisfaction and work motivation have a positive influence on performance, while the simultaneous test (F-test) showed that the two factors together significantly affect employee performance. The conclusion of this study confirms that increased job satisfaction and motivation can improve driver performance. Therefore, company management is advised to develop strategies that can increase employee satisfaction and motivation to increase productivity and operational effectiveness